2014
DOI: 10.1371/journal.pone.0097383
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin Induces Apoptosis of Lactotropes in Female Rodents

Abstract: Anterior pituitary cell turnover occurring during female sexual cycle is a poorly understood process that involves complex regulation of cell proliferation and apoptosis by multiple hormones. In rats, the prolactin (PRL) surge that occurs at proestrus coincides with the highest apoptotic rate. Since anterior pituitary cells express the prolactin receptor (PRLR), we aimed to address the actual role of PRL in the regulation of pituitary cell turnover in cycling females. We showed that acute hyperprolactinemia in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 79 publications
(153 reference statements)
0
38
0
Order By: Relevance
“…It has been suggested that PRL inhibits lactotrope functions directly within the pituitary in a dopamine-independent fashion [1]. We have previously shown that PRL increases apoptosis and reduces proliferation of lactotropes [2, 3]. Pharmacologically induced acute hyperprolactinemia also increases apoptosis and decreases proliferation of lactotropes.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…It has been suggested that PRL inhibits lactotrope functions directly within the pituitary in a dopamine-independent fashion [1]. We have previously shown that PRL increases apoptosis and reduces proliferation of lactotropes [2, 3]. Pharmacologically induced acute hyperprolactinemia also increases apoptosis and decreases proliferation of lactotropes.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, the chronic exposure of mice to a pure PRL receptor (PRLR) antagonist (Δ1–9-G129R-hPRL) increases lactotrope proliferation, leading to cell hyperplasia and increased pituitary weight [2]. We also observed that before tumor development, PRLR-deficient mice exhibit alterations in pituitary cell turnover, including decreased apoptotic rate [3]. Taken together, these data indicate that PRL acts as a proapoptotic and antiproliferative factor in lactotropes, which is critical to maintain anterior pituitary cell homeostasis [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, PRL is associated with immunoregulation, homeostatic maintenance, and tumorigenesis (Bernichtein et al, 2010;Horseman and Gregerson, 2013;Lopez-Pulide et al, 2013). Studies conducted to date have shown that PRL plays central roles in a wide range of biology processes, and all those actions are mediated by the specific cell surface receptor, the prolactin receptor (PRLR), which belongs to the superfamily of hematopoietic cytokine receptors (Ormandy et al, 1997a), combined with PRL activating several signaling pathways, including Janus Kinase-Signal transducer and activator of transcription ( Jak-Stat), mitogen-activated protein kinases (MAPK), and the phosphoinositide 3 kinase (PI3K), and resulting in endpoints such as differentiation, proliferation, survival and secretion (Kelly et al, 2001;Ferraris et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This hormone has manifold functions: immunological (Freeman et al, 2000), reproductive (Fitzgerald and Dinan, 2008;Egli et al, 2010), growth (Mosa et al, 2015), metabolic (Ben-Jonathan and Hugo, 2015) and behavioral (Babic et al, 2015). Moreover, it can be implicated in breast cancer (Surazynski et al, 2013) and in the regulation of cell proliferation and apoptosis (Ferraris et al, 2014;Hsieh et al, 2014) as well as the prostate gland activity (Rojas-Dur an et al, 2015). Synthesis and secretion of this lactogenic hormone are subjected to multiple regulators.…”
Section: Introductionmentioning
confidence: 99%